2019
DOI: 10.1158/0008-5472.can-18-3622
|View full text |Cite
|
Sign up to set email alerts
|

CBP/p300 Drives the Differentiation of Regulatory T Cells through Transcriptional and Non-Transcriptional Mechanisms

Abstract: Regulatory T cells (Treg) are immunosuppressive and negatively impact response to cancer immunotherapies. CREBbinding protein (CBP) and p300 are closely related acetyltransferases and transcriptional coactivators. Here, we evaluate the mechanisms by which CBP/p300 regulate Treg differentiation and the consequences of CBP/p300 loss-of-function mutations in follicular lymphoma. Transcriptional and epigenetic profiling identified a cascade of transcription factors essential for Treg differentiation. Mass spectrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
1
21
1
Order By: Relevance
“…However, our data would suggest the opposite, that PGI2 stimulation of IP results in β-catenin activation leading to its complexing with its transcriptional coactivator CBP resulting in enhanced Treg differentiation. As a whole, their overarching conclusion that PGI2 as well as CBP/p300 signaling is important for Treg differentiation supports our findings (69).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, our data would suggest the opposite, that PGI2 stimulation of IP results in β-catenin activation leading to its complexing with its transcriptional coactivator CBP resulting in enhanced Treg differentiation. As a whole, their overarching conclusion that PGI2 as well as CBP/p300 signaling is important for Treg differentiation supports our findings (69).…”
Section: Discussionsupporting
confidence: 87%
“…We were unable to confirm expression of PTGIS within Treg by Western blot or PCR (Supplemental Figure 14). Interestingly the authors were unable to find a direct effect of the PGI2 analog iloprost on Treg differentiation and concluded that CBP/p300 functions upstream of IP receptor stimulation and increased production of endogenous PGI2 mediates the effect of PTGIS on Treg differentiation via CBP/p300 (69). However, our data would suggest the opposite, that PGI2 stimulation of IP results in β-catenin activation leading to its complexing with its transcriptional coactivator CBP resulting in enhanced Treg differentiation.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…CBP/p300 are closely related acetyltransferases and transcriptional coactivators. CBP/p300 acetylates prostacyclin synthase, which regulates Tregs differentiation by altering pro-inflammatory cytokine secretion by T and B cells in follicular lymphoma [ 113 ]. The pro-autophagy protein AMBRA1 is also a key modulator of T cells, regulating the complex network that leads to human Tregs differentiation and maintenance.…”
Section: New Function and Regulatory Mechanisms For Tregsmentioning
confidence: 99%
“…The reversible acetylation of lysine residues on histone tails is mediated by histone acetyltransferases (HATs) [ 156 ], including the CBP/p300 family of HATs [ 157 ]. The function of CBP/p300 has been elucidated in late T cell differentiation [ 158 , 159 ], but not much is known about their function during earlier stages. They acted as transcriptional coactivators, and deletion of either CBP or p300 resulted in a reduction of DP thymocytes, but the double knockout showed a more drastic decrease in the number of mature T cells [ 120 ].…”
Section: Functions For Epigenetic Regulators In Early T Cell Developmentmentioning
confidence: 99%